Demodex spp. (Acari: Demodicidae) Infestation in Humans: Diagnostic Clues and Therapeutic Approaches to Primary and Secondary Demodicosis. - Atul Khajuria (International Journal of Insects, 2026)
Demodicosis represents an inflammatory dermatosis and adnexal disorder arising from pathologic overgrowth of Demodex mites, primarily Demodex folliculorum and Demodex brevis, which are ubiquitous human ectoparasites residing in pilosebaceous units and eyelid margins. Once regarded as benign commensals, these mites are now recognized as primary drivers or key cofactors in diverse clinical phenotypes, including papulopustular eruptions, pityriasis folliculorum, rosacea-like disorders, blepharitis, meibomian gland dysfunction, and exacerbations of comorbid dermatoses such as seborrheic dermatitis and perioral dermatitis. Epidemiologic data reveal near-universal infestation in adults, with mite density escalating with age (>90% prevalence in those over 70), immunosuppression (e.g., HIV, corticosteroids), seborrheic skin, and poor hygiene, potentially accounting for over two-thirds of blepharitis cases in select populations. Pathogenetically, D. folliculorum colonizes superficial follicles while D.brevis penetrates deeper sebaceous and meibomian glands, inducing tissue injury via mechanical duct obstruction by chitinous exoskeletons, foreign-body granulomatous reactions to mite remnants, microbial dysbiosis (e.g., vectoring Bacillus oleronius), and dysregulated host immunity involving TLR2-mediated cytokine storms (IL-17, IL-8) and impaired cellular clearance. Clinically, ocular demodicosis manifests with cylindrical lash dandruff, itching, lid erythema, and dry eye, while cutaneous forms exhibit polymorphic scaling, papulopustules, or nodular inflammation, often mimicking rosacea sans phymatous changes; dermoscopy reveals pathognomonic Demodex tails (60%) and follicular openings (70%). Diagnosis hinges on demonstrating elevated mite density (>5/cm² via standardized skin surface biopsy [SSSB], sensitivity ~90%), supplemented by epilation microscopy for ocular cases, dermoscopy, confocal microscopy, or PCR for research settings; response monitoring prioritizes density reduction and symptom amelioration over eradication. Management paradigms emphasize targeted acaricides—topical ivermectin 1% (daily, 12-16 weeks; ~70% mite reduction, 80% negativity rate), permethrin, tea tree oil derivatives, or metronidazole—alongside meticulous lid/skin hygiene, occlusive avoidance, and hot linens washing; oral ivermectin (200 µg/kg weekly) reserves for refractory, extensive, or immunocompromised disease, with relapse mitigation via maintenance. This synthesis distills contemporary insights into demodicosis epidemiology (>100% adult carriage, age/ immunosuppression risks), multifactorial pathogenesis, broad-spectrum phenotypes, refined in vivo diagnostics, and evidence-based acaricidal regimens, underscoring its underdiagnosis across dermatology, ophthalmology, and primary care. Enhanced awareness, via routine SSSB/dermoscopy integration, promises superior outcomes in recalcitrant facial/ocular inflammation, bridging microbiome-parasite-host interactions for clinicians, microbiologists, and researchers.
Keywords: Demodex brevis; Demodex folliculorum; Keywords: Demodicosis; acaricidal therapy; blepharitis; ivermectin; rosacea-like eruption; standardized skin surface biopsy